Friends recommendation on social networks - Rahman Syukri Othman (2019)
Social networks like Facebook and Twitter are prevailing nowadays. People use social networks to stay up-to-date with news and current events. Besides that, most people use social network so that they can make new friends. Friends recommendation on social networks is vital as it allow people to build better relationships as well as promoting information sharing and spreading.